(untitled) (International Journal of Engineering and Computer Science, 2016)
The new and eruptive dimension in consumerism today is caused by the rise of e-commerce. As the willingness and retention of purchasing online by a customer are rising so does it increase the amount of risks involved in the transactions involved. To tackle such problems the new age research have come up with many methods to compute the level of trust and confidence that can be invested into an entity. While the social media rises it has now become a pressing need for organizations to involve various trust mechanisms in their core businesses.